Effect of overlap length on the strength of adhesive joints of steel sheets - Doluk, Elżbieta; Rudawska, Anna; Miturska-Barańska, Izabela; Ogrodniczek, Jacek (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2022)
The study evaluates the shear strength of the single-lap adhesive joints made of C45 carbon steel. The influence of the overlap length on the shear strength of the adhesive joint was tested. The elongation of the samples was also tested. Before the bonding process, the samples were treated with P180 abrasive paper and degreased. The adhesive joints were made using the Epidian 53/Z1/100:10 adhesive composition. The strength tests were carried out on a Zwick/Roell Z150 testing machine. The maximum value of the shear strength was obtained for the lap Lz1 = 13 mm and the minimum for Lz4 = 19 mm. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)